Expression of leptin and leptin receptor transcript in ovine corpus luteum - Mozaffar Karimzadeh Koshkghazi; Abbas Parham (Iranian Journal of Veterinary Medicine, 2018)
Background: Leptin, the product of the obesity (ob) gene, acts as a signaling adipokine for modulating food intake, energy metabolism and reproductive functions in mammals. Leptin’s effects on the reproductive system at various levels of the hypothalamic-pituitary-gonadal axis have been established. Moreover, the direct and local effect of leptin on bovine oocyte maturation and corpus luteum function has been determined. Objectives: Due to species differences, this study was designed to investigate expression of leptin mRNA as well as its long isoform receptor (Ob-Rb) mRNA in sheep corpus luteum. Methods: Ovaries of sheep containing mature corpus luteum were collected in the reproductive season from abattoirs. Total RNA of corpus luteum was extracted, cDNA synthesis was carried out subsequently and PCR reaction was performed using primers which were designed specifically for each gene. Beta-actin was used as housekeeping gene to verify reactions, and adipose tissue was selected as positive sample for expression of leptin and leptin receptor. Results: Gel electrophoresis of PCR products showed the amplification of 162 and 121-bp amplicons in all samples for leptin and leptin receptor respectively. Moreover, sequencing the amplified fragments and blasting them confirmed the accuracy of results. Conclusion: Our findings confirm the expression of leptin and its functional receptor transcripts in ovine corpus luteum. More studies for determining leptin effects on corpus luteum are guaranteed.